A Partially Rated LC Trap Type AC Filter for Grid-Tied Voltage Source Converters - Srinivas Gulur; Vishnu Mahadeva Iyer; Subhashish Bhattacharya (IEEE Open Journal of Power Electronics)
$AC$ power filters play an important role in limiting the high-frequency current harmonics injected by grid-tied voltage source converters (VSCs). Amongst the various types of filters, $LCL$ filters with integrated $LC$ traps have become popular due to their ability to achieve a size reduction of the grid side inductor while demonstrating a similar current harmonic mitigation performance as a traditional $LCL$ filter. In this article, a passively damped filter network with a partially rated $LC$ trap (also referred to as the $L\text{-}PT\text{-}L$ filter) is proposed and delineated. The proposed $L\text{-}PT\text{-}L$ filter provides a $-60\;\text{dB/dec}$ roll-off characteristics at frequencies greater than switching frequency. Additionally, it is also demonstrated that this proposed $L\text{-}PT\text{-}L$ filter has smaller voltage ratings for two of its shunt-connected capacitor components due to the specific placement of the damping resistor. A systematic analysis of the proposed $L\text{-}PT\text{-}L$ filter is elucidated to design and select the component parameters. Steady-state and transient experimental results captured from a grid-tied 2-Level, 3 $φ$ VSC prototype are provided to validate the grid current harmonic filtering capability, reduced voltage ratings of the two shunt capacitors and passive damping performance of the proposed $L\text{-}PT\text{-}L$ filter. The proposed approach can achieve 19% and 36% filter shunt branch volume reduction for low voltage (208 V, 60 Hz) and medium voltage (4.16 kV, 60 Hz) grid-tied inverter systems, respectively, compared to state-of-the-art $LCL$ filters with integrated $LC$ traps.